Balanced Polymorphisms and the Evolution of Dominance - Otto, Sarah P; Bourguet, Denis (The American naturalist, 1999)
We explore the evolution of dominance at polymorphisms maintained either by overdominant selection or by migration-selection balance. At such balanced polymorphisms, heterozygotes remain at appreciable frequencies over long periods of time, allowing extensive modification of dominance to occur. The strength of selection favoring a modifier of dominance is roughly proportional to the probability that a modifier allele is found in a heterozygote at the locus subject to balancing selection times the heterozygote fitness increase caused by the modifier. Using a two-locus model, we elucidate the interesting ways in which recombination and migration cause departures from this rough expectation. For example, with overdominance, a genetic association with the rarest allele favors a modifier that increases heterozygote fitness because the modifier occurs more often in heterozygotes. With migration-selection balance, dominance evolves more readily in patches experiencing the strongest selection. We also find that, while there are more heterozygotes in sink populations (which have higher rates of immigration than emigration), selection for dominance in sink and source populations is nearly equal because sink populations make a lower genetic contribution to future generations. We conclude that the evolution of dominance is likely to occur whenever polymorphism is maintained by either overdominance or migration.